THE CONTRADICTION OF HADITH AHAD WITH QIYAS AND ITS LEGAL IMPLICATIONS FOR GHAYR MUSAMMA DOWRY DEBTS AFTER THE HUSBAND'S DEATH BEFORE CONSUMMATION - Ahmad Zuhairuz Zaman; Zaenal Abidin Mochamad Baqir (MAHAD ALY JOURNAL OF ISLAMIC STUDIES, 2025)
Hadith Ahad is a hadith whose number of rawi in each ţabaqah or one of them is limited. In using hadith ahad related to legal issues, according to the majority of ulama', it is obligatory to practice it. However, some others reject hadith ahad in several cases such as in the context of ’umum al-balwa or when it contradicts qiyas. This study is a library research with a qualitative approach and uses content analysis methodology. This study aims to reveal the contradiction of hadith ahad with qiyas and its impact on the law of dowry that has not been determined by the husband when the marriage contract takes place, and then the husband dies before having intercourse with his wife. This study concluded that if the ‘illat qiyas is extracted from the evidence that is qaţ'iy, while the hadith that contradicts qiyas is the category of hadith ahad, then there is a khilaf. And this difference of opinion has an impact on the issue of dowry that has not been determined by the husband when the marriage contract takes place, then the husband dies before having intercourse with his wife. The opinion of the majority of fuqaha’ is that the wife has the right to receive mitsil dowry and inheritance based on the hadith ahad narrated by Ibn Mas'ud. While the opinion of the Malikiyah is that the wife does not get mut’ah, and does not get a dowry but the wife gets an inheritance based on qiyas in the sale and purchase.